EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE PADA MATERI PECAHAN KELAS VII SMP - Maulida, Maulida; Hamdani, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effectiveness of the cooperative learning model Think Pair Square type on fraction counting operations material. The method used in this study is experiment method and pre-experimental research with one-shot case study design. The aspect used to determine the effectiveness of learning using a cooperative model of Think Pair Square type is the implementation of learning, student activities and student learning outcomes. Data collection techniques used were measurements and observation sheets. The data collection tool used is a test of student learning outcomes, which contains 6 essay questions, learning implementation observation sheets and observation sheets for student activities. The research data were analyzed descriptively. The results obtained are the implementation of learning with a good category, the activity of students classified as active and the learning outcomes of students complete in a classical manner. Because all effectiveness criteria are fulfilled, the cooperative learning model of think pair square type on fractional counting operating material is effectively used in class VII SMP N 9 Pontianak.Â Keyword: Effectiveness of Learning, Cooperative Type of Think Pair Square Model, Fraction.